(untitled) - Coicaud, Jean-Marc (Cambridge, 2002)
In recent years instances of corruption, extremism, and public distruct have increasingly raised the question of political legitimacy. Jean-Marc Coicaud examines the issueby looking at the conditions necessary for a 'rule of law' to exist. He argues that in a democracy the greater the powers given to a political leader, the greater that leader's responsibilities toward society. In order to enjoy legitimacy therefore, our rulers must assume these responsibilities and be held account for them. This book will be of interest to political and social theorists and political philosophers
Keywords: Legitimacy of governments,Political obligation,Nghĩa vụ chính trị